Grammar Sections of EFL Classroom Tests in Secondary Schools from Tucumán - Abboud, Jorge (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
One interesting approach to gain an insight into the treatment of grammar in our classrooms consists of analyzing the test tasks we design to assess it. This article presents a study on the grammar sections of 60 EFL written tests used in secondary schools from Tucumán. The study includes an analysis of the design (based, mainly, on Bachman and Palmer, 1996) and the tasks included (based, partly, on Celce-Murcia, 2005; Larsen-Freeman, 2003, 2009 and Purpura, 2004). The analysis of the design of the grammar section considers its inclusion, relative salience and location. In turn, the tasks are classified according to context and type of response. Results show certain inconsistency in the design of test sections and a tendency to present decontextualized grammar tasks that elicit explicit knowledge about form. These findings may serve as a basis on which to make informed decisions regarding the teaching and testing of grammar.